Lineage- and Sex-Dependent Behavioral and Biochemical Transgenerational Consequences of Developmental Exposure to Lead, Prenatal Stress, and Combined Lead and Prenatal Stress in Mice - Sobolewski, Marissa (Environ Health Perspect, 2020)
BACKGROUND: Lead (Pb) exposure and prenatal stress (PS) during development are co-occurring risk factors with shared biological substrates. PS has been associated with transgenerational passage of altered behavioral phenotypes, whereas the transgenerational behavioral or biochemical consequences of Pb exposure, and modification of any such effects by PS, is unknown. OBJECTIVES: The present study sought to determine whether Pb, PS, or combined Pb and PS exposures produced adverse transgenerational consequences on brain and behavior. METHODS: Maternal Pb and PS exposures were carried out in F0 mice. Outside breeders were used at each subsequent breeding, producing four F1-F2 lineages: [F1 female-F2 female (FF), FM (male), MF, and MM]. F3 offspring were generated from each of these lineages and examined for outcomes previously found to be altered by Pb, PS, or combined Pb and PS in F1 offspring: behavioral performance [fixed-interval (FI) schedule of food reward, locomotor activity, and anxiety-like behavior], dopamine function [striatal expression of tyrosine hydroxylase (Th)], glucocorticoid receptor (GR) and plasma corticosterone, as well as brain-derived neurotrophic factor (BDNF) and total percent DNA methylation of Th and Bdnf genes in the frontal cortex and hippocampus. RESULTS: Maternal F0 Pb exposure produced runting in F3 offspring. Considered across lineages, F3 females exhibited Pb-related alterations in behavior, striatal BDNF levels, frontal cortical Th total percentage DNA methylation levels and serum corticosterone levels, whereas F3 males showed Pb- and PS-related alterations in behavior and total percent DNA methylation of hippocampal Bdnf. However, numerous lineage-specific effects were observed, most of greater magnitude than those observed across lineages, with outcomes differing by F3 sex. DISCUSSION: These findings support the possibility that exposures of previous generations to Pb or PS may influence the brain and behavior of future generations. Observed changes were sex-dependent, with F3 females showing multiple changes through Pb-exposed lineages. Lineage effects may occur through maternal responses to pregnancy, altered maternal behavior, epigenetic modifications, or a combination of mechanisms, but they have significant public health ramifications regardless of mechanism. https://doi.org/10.1289/EHP4977